Social Capital Strategies and Political Environment in Strengthening Community Risk Management: A Literature Review on Adaptive and Responsive Empowerment Models - Haryanto; Rina Rosviana; Hadi Supratikta (Journal for Lesson and Learning Studies, 2025)
In an increasingly complex risk landscape, community-based risk management requires adaptive and responsive approaches. Literature highlights the crucial role of social capital, yet its effectiveness is significantly influenced by the local political environment. This study aims to analyze social capital strategies within political contexts to strengthen adaptive and responsive community empowerment models. The method employed is a Systematic Literature Review (SLR) following the PRISMA guidelines, focusing on articles published between 2020-2024 from indexed databases such as Scopus and ScienceDirect. The review results identify five main themes: the role of social capital in collective cooperation, the influence of political governance, knowledge exchange, socio-economic empowerment, and an integrative model. The synthesis demonstrates that community resilience is most effective when social capital (such as trust and networks) interacts synergistically with inclusive and responsive governance. The proposed adaptive-responsive empowerment model emphasizes the integration of bottom-up community initiatives and top-down support from formal policies and institutions. In conclusion, aligning social structures with political institutions is key to building a sustainable community resilience framework in the face of evolving risks.